Editoras universitárias na internet: um estudo em Belém (PA) - SANTOS, Ivone de Lourdes Rodrigues dos (2023)
The study focuses on university publishers, aiming to understand how they contribute to the dissemination of knowledge in society and how they use the Internet in the dissemination and sales of their works. The work was conducted through bibliographic and documentary research, with data obtained from the website of the following publishers of public higher education institutions in Belém, Pará, Brazil: Editora da Universidade do Estado do Pará - EDUEPA; Editora of the Federal University of Pará - EDUFPA; and Editora of the Rural University of the Amazon - EDUFRA. Although profit is not the main objective of these publishers, it was found that technology is an important ally for their success, especially in the dissemination of knowledge produced within universities. By using the Internet to publicize the works they edit, university publishers show that it is not possible to promote the wide dissemination of their editorial products without breaking the geographical isolation through the use of resources that make remote sales possible.